Enabling Climate Change Adaptation in Coastal Systems: A Systematic Literature Review - Cabana, David; Rölfer, Lena; Evadzi, Prosper; Celliers, Louis (Earth's future, 2023)
Climate change poses increasingly severe risks for coastal ecosystems and coastal communities all around the globe. This condition requires implementing climate adaptation policy and advancing scientific knowledge to adapt to the current and future climate risks. However, implementing climate adaptation policy in coastal areas is still in its infancy. This paper provides insight into 650 peer‐reviewed empirical research studies on coastal climate adaptation from the past two decades, providing global evidence on the status quo and distilling six relevant research gaps: (a) minimal contribution to the implementation phase of the adaptation policy cycle; (b) geographical imbalance toward specific ecoregions and coastal sub‐systems; (c) less attention to regional scale; (d) lack of sectoral integration; (e) poor contextualization within policy and coastal governance instruments and management arrangements; (f) limited economic and financial focus. Therefore, this paper identifies areas where future empirical research can help fill current knowledge gaps and improve coastal communities' ability to adapt to climate change. This increased knowledge will enhance the resilience of coastal social‐ecological systems in the face of environmental challenges. Plain Language Summary Coastal regions are complex environments and are severely threatened by climate change. These regions are particularly vulnerable to rising sea levels, more frequent and intense storms, altered precipitation patterns, and higher ocean temperatures. These changes can pose pervasive threats to coastal communities, ecosystems, infrastructure, and economic activities. This manuscript reviews the last 20 years of coastal adaptation science and provides evidence of six areas where further research is needed. In our analysis, we adopt a worldwide scale and multidisciplinary perspective to review 650 publications and draw some conclusions and recommendations around which science could benefit coastal adaptation to climate change. Overall, we find a geographical imbalance of knowledge production which mostly neglects the global south, and that science needs to boost cooperation across borders and economic sectors and services. Key Points Scientific contribution to the adaptation policy cycle needs an implementation perspective Adaptation research must advance knowledge in highly climate‐sensitive ecoregions, across borders and sectors Economic barriers to coastal adaptation have been overlooked globally